GAMBARAN PENGETAHUAN, SIKAP, DAN PERILAKU MASYARAKAT TENTANG UPAYA PENCEGAHAN PENYAKIT DBD DI KELURAHAN KENTENG BANJARNEGARA - Joko Malis Sunarno; Dwi Atin Faidah (Jurnal Ilmiah Medsains, 2021)
Dengue Hemorrhagic Fever (DHF) is a disease caused by the dengue virus which is transmitted from person to person through the bite of the Aedes sp. The results of the preliminary survey found that in recent years the incidence of dengue fever has always occurred repeatedly in Kenteng Village. The purpose of this study was to describe the knowledge, attitudes, and behavior of the community regarding efforts to prevent dengue fever in Kenteng Village, Madukara Sub-District, Banjarnegara District in 2021. This is an observational study with cross sectional approach. The sample population is the family head of Kenteng Village, Madukara Sub-District, Banjarnegara Dsitrict. The number of samples after being determined by the Slovin formula is 74 respondents who will be selected by simple random sampling. The results showed that most of the respondents were in the age group of 20-40 years (47.3%), the education level was elementary school graduates (43.3%), having the type of work as housewives or not working (39.2%), and have a monthly income below the UMK (60.8%). While the knowledge of attitudes and behavior of respondents about prevention of DHF is mostly sufficient knowledge (82.4%), have a good attitude (78.4%) and have positive behavior (93.2%). Although most of the respondents' knowledge, attitudes and behavior were classified as good, there was still a need for regular socialization because the incidence of DHF always repeated in every season.